POTENSI DARI EKSTRAK DAN FRAKSI KULIT BUAH MUNDAR (Garcinia forbesii) SEBAGAI TABIR SURYA BERDASARKAN NILAI SUN PROTECTION FACTOR (SPF) - Muhammad Ikhwan Rizki; Samsul Hadi; Lutfi Chabib (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
UV rays cause skin damage such as loss of skin elasticity, wrinkles, sagging, and skin cancer. South Kalimantan is a wetland area with more than 4,000 species of medicinal plants. Mundar (Garcinia forbesii) is one of the plants in South Kalimantan. Mundar pericarp is empirically used for cosmetics which is believed to protect the skin from ultraviolet rays. The purpose of the study was to determine the sunscreen potency of the extract and fraction from pericarp of mundar (Garcinia forbesii) based on the Sun Protection Factor (SPF) parameter. The research started from material drying, making simplicia powder, extraction, and fractions. The extracts and fractions were measured for SPF values ??using a UV-Vis Spectrophotometer. The results showed that the ethanol extract and ethyl acetate fraction had weak protection, while the n-hexane fraction had extreme protective power with SPF values ??in the range of 6.51 – 30.00